Analisis Dampak Pengembangan Pariwisata terhadap Ekonomi Masyarakat di Desa Lantan Kec, Batukliang Utara, Kab, Lombok Tengah - Imran Imran; Irwan Irwan (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This study aims to explore in depth the economic impact experienced by the community as a result of tourism development in Lantan Village, as well as the social impacts arising from these activities on the local residents. This research is expected to serve as a useful medium for sharing the author’s knowledge regarding the analysis of the impact of tourism development on the economy and social life of the community in Lantan Village, Batukliang Utara District, Central Lombok Regency. The research employs a qualitative approach using a case study strategy, where primary data were collected through in-depth interviews with tourism business actors, MSME entrepreneurs, and community leaders directly involved in tourism activities in Lantan Village. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results of the study indicate that most informants gave positive responses toward the presence of tourism, as it has increased community income and expanded employment opportunities. In addition, tourism development has brought significant social impacts, such as enhanced social interaction, changes in lifestyle, and a growing awareness among the community about the importance of preserving the local environment and culture amidst the ongoing development of the tourism sector.